Seminar PAUD Inklusi: Mengenal Lebih Dekat Anak Berkebutuhan Khusus di Kabupaten Gowa - Fitriani Dzulfadhilah; Sitti Nurhidayah Ilyas; Rika Kurnia R; Sri Rika Amriani H; Angri Lismayani (Jurusan Teknik Informatika dan Komputer, 2023)
The community service activity carried out was an Inclusive ECE seminar with the topic of getting to know children with special needs more closely. This community service program was held at Melati Kindergarten, Gowa Regency. The seminar participants were 12 people consisting of 6 teachers, 1 principal and 5 students who were conducting the MBKM Independent Study program at Melati Kindergarten, Gowa Regency. This service program aims to make teachers and principals more familiar with special needs children and how to handle them. The implementation methods used in this service are presentation, lecture, and discussion methods. The results of this service activity were measured using a pre-test and post-test given to participants to determine the increase in understanding before and after being given inclusive education seminar material. The data collected was then analyzed using the Wilcoxon Test with the help of SPSS, the results of which showed that the data Asymp (2-tailed) = 0.01 <0.05, meaning that there was a significant difference between the participants' understanding before and after being given the Inclusive ECE Seminar. The results of the service showed an increase in awareness of children with special needs, an increase in participants' understanding of the types of children with special needs, and also an increase in participants' understanding of the treatment that can be done for children with special needs.